Coating for offshore wind power as well as preparation method and application of coating

By developing special coatings for offshore wind power without fluorine, using polymers with specific structures and flake zinc powder and other components, combined with the use of acid anhydride curing agent and cationic curing agent, the corrosion resistance and environmental friendliness of existing coatings in extreme environments are solved, and the coating performance is achieved with high weather resistance and environmentally friendly.

CN119684850APending Publication Date: 2025-03-25HEBEI GUANGXING SEMICON TECH CO LTD

Patent Information

Application Number
CN202411986025.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-31
Publication Date
2025-03-25

AI Technical Summary

Technical Problem

Existing offshore wind power coatings are not corrosion-resistant, adhesion and weather-resistant in extreme marine environments, and most coatings contain fluoride, which affects the environment and ecology.

Method used

Develop a special coating for offshore wind power without fluorine, using polymers with specific structures, flake zinc powder and additives, prepared by polymerization and mixing processes, combining the use of anhydride curing agent and cationic curing agent to form a coating with excellent heavy corrosion resistance.

Benefits of technology

It achieves high weather resistance, corrosion resistance and temperature adaptability of the coating, and is environmentally friendly and does not contain harmful fluoride, which significantly improves the durability and safety of offshore wind power equipment.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005223137290000021
    Figure BDA0005223137290000021
  • Figure BDA0005223137290000031
    Figure BDA0005223137290000031
  • Figure BDA0005223137290000141
    Figure BDA0005223137290000141
Patent Text Reader

Abstract

The invention relates to a coating for offshore wind power as well as a preparation method and application thereof. The coating comprises a component A and a component B, the component A comprises a polymer, flaky zinc powder and an auxiliary agent, and the polymer comprises a structural unit A shown in a formula (I), a structural unit B shown in a formula (II), a monovinyl aromatic hydrocarbon structural unit and a diene structural unit; on the basis of the weight of the polymer, the content of the structural unit A as shown in the formula (I) is 10-50 wt%, the content of the structural unit B as shown in the formula (II) is 0.1-2 wt%, the content of the monovinylarene structural unit is 30-60 wt%, and the content of the diene structural unit is 18-40 wt%; wherein the component B is a curing agent. The coating does not contain fluorine, is environment-friendly, and has good weather resistance, good corrosion resistance, good temperature adaptability and excellent heavy corrosion resistance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of wind power, and in particular to a coating for offshore wind power, a preparation method thereof and an application thereof. Background Art

[0002] With the global emphasis on renewable energy, offshore wind power has been widely used as a clean and renewable energy form. Offshore wind power equipment is usually placed in a harsh marine environment and faces erosion from a variety of environmental factors such as strong winds, salt spray, high humidity and low temperatures, which puts higher demands on its durability and safety. Therefore, in order to ensure the long-term and stable operation of offshore wind power equipment, its surface coating is required to have excellent heavy-duty anti-corrosion performance.

[0003] Although there are many anti-corrosion coatings in use in the current market, the corrosion resistance, adhesion and weather resistance of most coatings in extreme marine environments are still not ideal. Especially after long-term use, coating aging, peeling and rusting are common. Or although the performance has been greatly improved, fluorine modification is used. Fluorine is not easy to digest and is enriched in the ocean, which affects the survival of marine life and pollutes the environment. For example, CN102093812B discloses an anti-corrosion, wear-resistant, anti-freeze and adhesive bottom surface all-in-one coating and a preparation method thereof. Specifically, the anti-corrosion, wear-resistant, anti-freeze and adhesive bottom surface all-in-one coating disclosed therein comprises the following ingredients in weight percentage: component A comprises: 10-40% isocyanate, 30-75% terminal amino polyether, 1-15% fluorine-containing silicone, and 5-25% anhydrous butyl acetate; component B comprises: 15%-55% hindered aliphatic secondary amine, 1%-15% nano antifreeze adhesive material, 10%-55% pigment filler, 0.5%-2.5% dispersant, 0-2% thixotropic agent, 0-3% ultraviolet absorber, and 5%-30% solvent. The anti-corrosion, wear-resistant, anti-freezing and bottom-to-bottom coating it provides is a two-component coating, including a curing agent component and an auxiliary component. It mainly adopts a spraying construction process to form a functional coating with good anti-corrosion effect, wear resistance, and anti-freezing adhesion. It is particularly suitable for heavy-duty vehicle painting and wind turbine blades and other occasions with high requirements for wear resistance, corrosion resistance, and anti-freezing adhesion. Although the fluorinated siloxane used has a certain degree of weather resistance, it is inevitable that fluorine will pollute the ocean, soil, and vegetation, affecting the ecological balance. Most countries are now developing non-fluorinated coatings with excellent performance.

[0004] Therefore, developing a non-fluorine-free offshore wind power coating with excellent heavy-duty anti-corrosion properties has become a technical problem that needs to be solved urgently. Summary of the invention

[0005] In view of the common problems in the prior art such as insufficient weather resistance, poor corrosion resistance, poor temperature adaptability and poor environmental friendliness, the purpose of the present invention is to provide a coating for offshore wind power and a preparation method and application thereof. The coating does not contain fluorine, is environmentally friendly, has good weather resistance, good corrosion resistance, good temperature adaptability, and has excellent heavy-duty anti-corrosion performance.

[0006] To achieve the above purpose, the first aspect of the present invention provides a coating for offshore wind power, comprising component A and component B, wherein component A comprises a polymer, flaky zinc powder and an additive, wherein the polymer contains a structural unit A represented by formula (I), a structural unit B represented by formula (II), a monovinyl aromatic structural unit and a diene structural unit; based on the weight of the polymer, the content of the structural unit A represented by formula (I) is 10-50% by weight, the content of the structural unit B represented by formula (II) is 0.1-2% by weight, the content of the monovinyl aromatic structural unit is 30-60% by weight, and the content of the diene structural unit is 18-40% by weight; wherein component B is a curing agent;

[0007]

[0008] Here, p is an integer from 1 to 6.

[0009] On the basis of the above technical solution, in the present invention, the monovinyl aromatic hydrocarbon structural unit may be but is not limited to styrene, vinyl toluene, α-methylstyrene, 4-tert-butylstyrene and 4-methylstyrene.

[0010] On the basis of the above technical solution, in the present invention, the diene structural unit may be but is not limited to butadiene, propadiene, 1,3-butadiene, 1,4-pentadiene and the like.

[0011] On the basis of the above technical solution, based on the total weight of component A, the content of the polymer is 20-50 weight %, the content of the flaky zinc powder is 30-60 weight %, and the content of the auxiliary agent is 10-30 weight %.

[0012] On the basis of the above technical solution, the auxiliary agent is selected from one or more of a dispersant, a thixotropic agent, a leveling agent, a defoaming agent, a coupling agent, an antioxidant and a curing accelerator.

[0013] On the basis of the above technical solution, the dispersant is selected from one or more of carboxylates, sulfate esters, sulfonates, quaternary ammonium salts and pyridinium salts.

[0014] On the basis of the above technical solution, the thixotropic agent is selected from organic bentonite and / or hydrogenated castor oil.

[0015] On the basis of the above technical solution, the leveling agent is selected from one or more of BYK-307, BYK-310, BYK-320 and BYK-333.

[0016] On the basis of the above technical solution, the defoaming agent is selected from BYK-072 and / or BYK-141.

[0017] Based on the above technical solution, the antioxidant is selected from antioxidant 168 and / or antioxidant 1010.

[0018] On the basis of the above technical solution, the coupling agent is selected from silane coupling agent.

[0019] On the basis of the above technical solution, the curing accelerator is selected from one or more of amines, phenols, substituted ureas, imidazoles and their salts, metal organic salts and phosphine compounds.

[0020] On the basis of the above technical solution, the curing agent is selected from anhydride curing agent and / or cationic curing agent.

[0021] On the basis of the above technical solution, the curing agent is selected from an anhydride curing agent and a cationic curing agent, and the weight ratio of the anhydride curing agent to the cationic curing agent is 1:0.2-0.6.

[0022] On the basis of the above technical solution, the acid anhydride curing agent is selected from one or more of phthalic anhydride, hexahydrophthalic anhydride, glutaric anhydride and dodecyl succinic anhydride.

[0023] On the basis of the above technical solution, the cationic curing agent is selected from one or more of amine salts, aromatic sulfonium salts, aromatic iodonium salts, aromatic phosphonium salts, aluminum complex curing agents, aromatic diazonium salts and pyridinium curing agents, such as but not limited to ammonium chloride, barium chloride, etc.

[0024] On the basis of the above technical solution, the weight ratio of component A to component B is 1:0.1-0.4.

[0025] The second aspect of the present invention provides a method for preparing the above-mentioned coating for offshore wind power, comprising:

[0026] Step 1, in the presence of an initiator, mixing a monomer having a structure represented by formula (III), a monomer having a structure represented by formula (IV), a monovinyl aromatic hydrocarbon structural unit and a diene structural unit to carry out a polymerization reaction to obtain a polymer, wherein the amount of the structural unit A represented by formula (III) is 10-50% by weight, the amount of the structural unit B represented by formula (IV) is 0.1-2% by weight, the amount of the monovinyl aromatic hydrocarbon structural unit is 30-60% by weight, and the amount of the diene structural unit is 18-40% by weight based on the weight of the polymer;

[0027]

[0028] Wherein, p is an integer from 1 to 6;

[0029] Step 2, mixing the polymer, flaky zinc powder and an additive to obtain component A;

[0030] Step 3: Mix component B with component A, wherein component B is a curing agent.

[0031] On the basis of the above technical solution, in the present invention, the monovinyl aromatic hydrocarbon structural unit may be but is not limited to styrene, vinyl toluene, α-methylstyrene, 4-tert-butylstyrene and 4-methylstyrene.

[0032] On the basis of the above technical solution, in the present invention, the diene structural unit may be but is not limited to butadiene, propadiene, 1,3-butadiene, 1,4-pentadiene and the like.

[0033] On the basis of the above technical solution, the initiator is selected from one or more of azobisisobutyronitrile, azobisisoheptanenitrile and dibenzoyl peroxide.

[0034] On the basis of the above technical solution, the conditions of the polymerization reaction include: temperature of 10-40° C. and time of 6-10 hours.

[0035] On the basis of the above technical solution, the auxiliary agent is selected from one or more of a dispersant, a thixotropic agent, a leveling agent, a defoaming agent, a coupling agent, an antioxidant and a curing accelerator.

[0036] On the basis of the above technical solution, the dispersant is selected from one or more of carboxylates, sulfate esters, sulfonates, quaternary ammonium salts and pyridinium salts.

[0037] On the basis of the above technical solution, the thixotropic agent is selected from organic bentonite and / or hydrogenated castor oil.

[0038] On the basis of the above technical solution, the leveling agent is selected from one or more of BYK-307, BYK-310, BYK-320 and BYK-333.

[0039] On the basis of the above technical solution, the defoaming agent is selected from BYK-072 and / or BYK-141.

[0040] Based on the above technical solution, the antioxidant is selected from antioxidant 168 and / or antioxidant 1010.

[0041] On the basis of the above technical solution, the coupling agent is selected from silane coupling agent.

[0042] On the basis of the above technical solution, the curing accelerator is selected from one or more of amines, phenols, substituted ureas, imidazoles and their salts, metal organic salts and phosphine compounds.

[0043] On the basis of the above technical solution, the curing agent is selected from anhydride curing agent and / or cationic curing agent.

[0044] On the basis of the above technical solution, the curing agent is selected from an anhydride curing agent and a cationic curing agent, and the weight ratio of the anhydride curing agent to the cationic curing agent is 1:0.2-0.6.

[0045] On the basis of the above technical solution, the acid anhydride curing agent is selected from one or more of phthalic anhydride, hexahydrophthalic anhydride, glutaric anhydride and dodecyl succinic anhydride.

[0046] On the basis of the above technical solution, the cationic curing agent is selected from one or more of amine salts, aromatic sulfonium salts, aromatic iodonium salts, aromatic phosphonium salts, aluminum complex curing agents, aromatic diazonium salts and pyridinium curing agents, such as but not limited to ammonium chloride, barium chloride, etc.

[0047] On the basis of the above technical solution, the weight ratio of component A to component B is 1:0.1-0.4.

[0048] A third aspect of the present invention provides application of the above-mentioned coating for offshore wind power in the field of offshore wind power.

[0049] Beneficial effects of the present invention:

[0050] (1) The present invention abandons relatively polluting fluorides and adopts more environmentally friendly sulfides as key ingredients, making the product more environmentally friendly. At the same time, the innovation of the present invention lies in the introduction of compounds with specific structures, namely compounds shown in Formula I and Formula II, which play a core role in the coating formulation. By adopting a sulfur-modified monomer design, performance optimization and improvement are achieved. Sulfur modification not only enhances the stability of the compound, but also further enhances the overall performance of the coating through the interaction between sulfur atoms and other components. In addition, by using the specific polymer of the present invention, combined with the use of flaky zinc powder and additives, the coating of the present invention has made significant progress in tolerance performance. Flaky zinc powder, due to its unique physical form, can form an effective shielding layer in the coating, enhancing the corrosion resistance and durability of the coating. The selection and application of additives further refine and optimize the various properties of the coating, such as improving adhesion, enhancing salt spray resistance and corrosion resistance.

[0051] (2) Anhydride curing agents are organic substances containing acid, and their acidity comes from the anhydride groups in their molecular structure. They can react with substances containing hydrogen atoms to initiate a curing reaction and form a strong and durable solid. Anhydride curing agents usually have low volatility and high activity. Coatings cured with anhydride curing agents usually have good weather resistance and chemical corrosion resistance, and can adapt to the complex weather conditions and chemical corrosion in the offshore wind power environment. Cationic curing agent is a new type of coating curing agent, which is non-toxic, odorless, solvent-free, environmentally friendly and will not pollute the environment. It has the characteristics of high strength, high hardness, wear resistance, chemical corrosion resistance and excellent weather resistance, and is a new high-tech product in the coating field. The heat and humidity resistance of epoxy resins obtained by curing with anhydride curing agents and cationic curing agents at the same time has unexpectedly improved. This is because anhydride curing agents cure epoxy resins according to a step-by-step polymerization mechanism, while cationic curing agents cure epoxy resins according to a chain polymerization mechanism. The combination of the two can form a more stable and heat-resistant coating structure. The offshore wind power environment is complex and changeable, and the performance requirements of coatings are high. The combined use of anhydride curing agent and cationic curing agent can improve the comprehensive performance of the coating and make it better adapted to the offshore wind power environment. However, the curing speeds of anhydride curing agent and cationic curing agent are different, so it is necessary to adjust the dosage ratio of the two. Prevent excessive use of a single component, resulting in degradation of epoxy resin performance. The ratio of the present invention, combined with other substances, can obtain a coating for offshore wind power with better performance. DETAILED DESCRIPTION

[0052] In the following technical description, for the sake of convenience of explanation, many details are provided to provide a full understanding of the disclosed embodiments. However, one or more embodiments can still be implemented without these details.

[0053] The terms "first", "second", etc. in the description and claims of the disclosed embodiments are used to distinguish similar objects, and are not necessarily used to describe a specific order or sequence. It should be understood that the terms used in this way can be interchanged where appropriate, so that the embodiments of the disclosed embodiments described herein. In addition, the terms "including" and "having" and any variations thereof are intended to cover non-exclusive inclusions.

[0054] The following are examples.

[0055] In the following examples, the raw materials were all purchased from commercial sources.

[0056] Example 1

[0057] Preparation of an anti-corrosion coating for offshore wind power:

[0058] Step 1: Under nitrogen protection, 30 g acrylamide, 1 g monomer (Formula IV, wherein p=2), 40 g styrene, 28.8 g butadiene and 0.2 g azobisisobutyronitrile were mixed and heated at 40° C. for 6 hours. The mixture was then cooled to room temperature, washed with acetone, and dried at 50° C. for 4 hours to obtain a polymer.

[0059] Step 2: 35 g of the polymer obtained in step 1, 50 g of flaky zinc powder, 3 g of YCK-2410 dispersant, 2 g of hydrogenated castor oil, 2 g of BYK-307 leveling agent, 2 g of BYK-141 defoamer, 2 g of antioxidant 168, 2 g of Y200 fumed silica coupling agent, and 2 g of DMP-30 curing accelerator are mixed to obtain component A.

[0060] Step 3: Mix 70 g of hexahydrophthalic anhydride curing agent and 30 g of ammonium chloride to obtain component B.

[0061] Step 4: Mix 100 g of component A with 30 g of component B to obtain a coating for offshore wind power.

[0062] Example 2

[0063] An anti-corrosion coating for offshore wind power generation was prepared according to the method of Example 1, except that the amount of the polymer substance was:

[0064] Step 1: Under nitrogen protection, 50 g acrylamide, 1 g monomer (Formula IV, wherein p=2), 30 g styrene, 18.8 g butadiene and 0.2 g azobisisobutyronitrile were mixed and heated at 40° C. for 6 hours. The mixture was then cooled to room temperature, washed with acetone, and dried at 50° C. for 4 hours to obtain a polymer.

[0065] Step 2: 35 g of the polymer obtained in step 1, 50 g of flaky zinc powder, 3 g of YCK-2410 dispersant, 2 g of hydrogenated castor oil, 2 g of BYK-307 leveling agent, 2 g of BYK-141 defoamer, 2 g of antioxidant 168, 2 g of Y200 fumed silica coupling agent, and 2 g of DMP-30 curing accelerator are mixed to obtain component A.

[0066] Step 3: Mix 70 g of hexahydrophthalic anhydride curing agent and 30 g of ammonium chloride to obtain component B.

[0067] Step 4: Mix 100 g of component A with 30 g of component B to obtain a coating for offshore wind power.

[0068] Example 3

[0069] An anti-corrosion coating for offshore wind power generation was prepared according to the method of Example 1, except that the amount of the polymer substance was:

[0070] Step 1: Under nitrogen protection, 20 g of acrylamide, 1 g of monomer (Formula IV, wherein p=2), 54 g of styrene, 24.8 g of butadiene and 0.2 g of azobisisobutyronitrile were mixed and heated at 40° C. for 6 hours. The mixture was then cooled to room temperature, washed with acetone, and dried at 50° C. for 4 hours to obtain a polymer.

[0071] Step 2: 35 g of the polymer obtained in step 1, 50 g of flaky zinc powder, 3 g of YCK-2410 dispersant, 2 g of hydrogenated castor oil, 2 g of BYK-307 leveling agent, 2 g of BYK-141 defoamer, 2 g of antioxidant 168, 2 g of Y200 fumed silica coupling agent, and 2 g of DMP-30 curing accelerator are mixed to obtain component A.

[0072] Step 3: Mix 70 g of hexahydrophthalic anhydride curing agent and 30 g of ammonium chloride to obtain component B.

[0073] Step 4: Mix 100 g of component A with 30 g of component B to obtain a coating for offshore wind power.

[0074] Example 4

[0075] An anti-corrosion coating for offshore wind power was prepared according to the method of Example 1, except that the amount of the substance in component A was:

[0076] Step 1: Under nitrogen protection, 30 g acrylamide, 1 g monomer (Formula IV, wherein p=2), 40 g styrene, 28.8 g butadiene and 0.2 g azobisisobutyronitrile were mixed and heated at 40° C. for 6 hours. The mixture was then cooled to room temperature, washed with acetone, and dried at 50° C. for 4 hours to obtain a polymer.

[0077] Step 2: 50 g of the polymer obtained in step 1, 35 g of flaky zinc powder, 3 g of YCK-2410 dispersant, 2 g of hydrogenated castor oil, 2 g of BYK-307 leveling agent, 2 g of BYK-141 defoamer, 2 g of antioxidant 168, 2 g of Y200 fumed silica coupling agent, and 2 g of DMP-30 curing accelerator are mixed to obtain component A.

[0078] Step 3: Mix 70 g of hexahydrophthalic anhydride curing agent and 30 g of ammonium chloride to obtain component B.

[0079] Step 4: Mix 100 g of component A with 30 g of component B to obtain a coating for offshore wind power.

[0080] Example 5

[0081] An anti-corrosion coating for offshore wind power was prepared according to the method of Example 1, except that the amount of the substance in component A was:

[0082] Step 1: Under nitrogen protection, 30 g acrylamide, 1 g monomer (Formula IV, wherein p=2), 40 g styrene, 28.8 g butadiene and 0.2 g azobisisobutyronitrile were mixed and heated at 40° C. for 6 hours. The mixture was then cooled to room temperature, washed with acetone, and dried at 50° C. for 4 hours to obtain a polymer.

[0083] Step 2: Mix 25 g of the polymer obtained in step 1, 60 g of flaky zinc powder, 3 g of YCK-2410 dispersant, 2 g of hydrogenated castor oil, 2 g of BYK-307 leveling agent, 2 g of BYK-141 defoamer, 2 g of antioxidant 168, 2 g of Y200 fumed silica coupling agent, and 2 g of DMP-30 curing accelerator to obtain component A.

[0084] Step 3: Mix 70 g of hexahydrophthalic anhydride curing agent and 30 g of ammonium chloride to obtain component B.

[0085] Step 4: Mix 100 g of component A with 30 g of component B to obtain a coating for offshore wind power.

[0086] Example 6

[0087] An anti-corrosion coating for offshore wind power was prepared according to the method of Example 1, except that the amount of the substance in component B was:

[0088] Step 1: Under nitrogen protection, 30 g acrylamide, 1 g monomer (Formula IV, wherein p=2), 40 g styrene, 28.8 g butadiene and 0.2 g azobisisobutyronitrile were mixed and heated at 40° C. for 6 hours. The mixture was then cooled to room temperature, washed with acetone, and dried at 50° C. for 4 hours to obtain a polymer.

[0089] Step 2: 35 g of the polymer obtained in step 1, 50 g of flaky zinc powder, 3 g of YCK-2410 dispersant, 2 g of hydrogenated castor oil, 2 g of BYK-307 leveling agent, 2 g of BYK-141 defoamer, 2 g of antioxidant 168, 2 g of Y200 fumed silica coupling agent, and 2 g of DMP-30 curing accelerator are mixed to obtain component A.

[0090] Step 3: Mix 80 g of hexahydrophthalic anhydride curing agent and 20 g of ammonium chloride to obtain component B.

[0091] Step 4: Mix 100 g of component A with 30 g of component B to obtain a coating for offshore wind power.

[0092] Example 7

[0093] An anti-corrosion coating for offshore wind power generation was prepared according to the method of Example 1, except that the amount of the polymer substance was:

[0094] Step 1: Under nitrogen protection, 30 g acrylamide, 5 g monomer (Formula IV, wherein p=2), 35 g styrene, 29.8 g butadiene and 0.2 g azobisisobutyronitrile were mixed and heated at 40° C. for 6 hours. The mixture was then cooled to room temperature, washed with acetone, and dried at 50° C. for 4 hours to obtain a polymer.

[0095] Step 2: 35 g of the polymer obtained in step 1, 50 g of flaky zinc powder, 3 g of YCK-2410 dispersant, 2 g of hydrogenated castor oil, 2 g of BYK-307 leveling agent, 2 g of BYK-141 defoamer, 2 g of antioxidant 168, 2 g of Y200 fumed silica coupling agent, and 2 g of DMP-30 curing accelerator are mixed to obtain component A.

[0096] Step 3: Mix 70 g of hexahydrophthalic anhydride curing agent and 30 g of ammonium chloride to obtain component B.

[0097] Step 4: Mix 100 g of component A with 30 g of component B to obtain a coating for offshore wind power.

[0098] Example 8

[0099] An anti-corrosion coating for offshore wind power was prepared according to the method of Example 1, except that the amount of the substance in component A was:

[0100] Step 1: Under nitrogen protection, 30 g acrylamide, 1 g monomer (Formula IV, wherein p=2), 40 g styrene, 28.8 g butadiene and 0.2 g azobisisobutyronitrile were mixed and heated at 40° C. for 6 hours. The mixture was then cooled to room temperature, washed with acetone, and dried at 50° C. for 4 hours to obtain a polymer.

[0101] Step 2: 5 g of the polymer obtained in step 1, 80 g of flaky zinc powder, 3 g of YCK-2410 dispersant, 2 g of hydrogenated castor oil, 2 g of BYK-307 leveling agent, 2 g of BYK-141 defoamer, 2 g of antioxidant 168, 2 g of Y200 fumed silica coupling agent, and 2 g of DMP-30 curing accelerator are mixed to obtain component A.

[0102] Step 3: Mix 70 g of hexahydrophthalic anhydride curing agent and 30 g of ammonium chloride to obtain component B.

[0103] Step 4: Mix 100 g of component A with 30 g of component B to obtain a coating for offshore wind power.

[0104] Example 9

[0105] An anti-corrosion coating for offshore wind power was prepared according to the method of Example 1, except that the amount of the substance in component B was:

[0106] Step 1: Under nitrogen protection, 30 g acrylamide, 1 g monomer (Formula IV, wherein p=2), 40 g styrene, 28.8 g butadiene and 0.2 g azobisisobutyronitrile were mixed and heated at 40° C. for 6 hours. The mixture was then cooled to room temperature, washed with acetone, and dried at 50° C. for 4 hours to obtain a polymer.

[0107] Step 2: 35 g of the polymer obtained in step 1, 50 g of flaky zinc powder, 3 g of YCK-2410 dispersant, 2 g of hydrogenated castor oil, 2 g of BYK-307 leveling agent, 2 g of BYK-141 defoamer, 2 g of antioxidant 168, 2 g of Y200 fumed silica coupling agent, and 2 g of DMP-30 curing accelerator are mixed to obtain component A.

[0108] Step 3: Mix 50 g of hexahydrophthalic anhydride curing agent and 50 g of ammonium chloride to obtain component B.

[0109] Step 4: Mix 100 g of component A with 30 g of component B to obtain a coating for offshore wind power.

[0110] Comparative Example 1

[0111] An anti-corrosion coating for offshore wind power was prepared according to the method of Example 1, except that acrylamide of formula III was not used and was replaced by a monomer of formula IV, namely:

[0112] Step 1: Under nitrogen protection, 31 g of monomer (Formula IV, wherein p=2), 40 g of styrene, 28.8 g of butadiene and 0.2 g of azobisisobutyronitrile were mixed and heated at 40° C. for 6 hours. The mixture was then cooled to room temperature, washed with acetone, and dried at 50° C. for 4 hours to obtain a polymer.

[0113] Step 2: 35 g of the polymer obtained in step 1, 50 g of flaky zinc powder, 3 g of YCK-2410 dispersant, 2 g of hydrogenated castor oil, 2 g of BYK-307 leveling agent, 2 g of BYK-141 defoamer, 2 g of antioxidant 168, 2 g of Y200 fumed silica coupling agent, and 2 g of DMP-30 curing accelerator are mixed to obtain component A.

[0114] Step 3: Mix 70 g of hexahydrophthalic anhydride curing agent and 30 g of ammonium chloride to obtain component B.

[0115] Step 4: Mix 100 g of component A with 30 g of component B to obtain a coating for offshore wind power.

[0116] Comparative Example 2

[0117] An anti-corrosion coating for offshore wind power was prepared according to the method of Example 1, except that the monomer of formula IV was not used and was replaced by acrylamide of formula III, that is:

[0118] Step 1: Under nitrogen protection, 31 g acrylamide, 40 g styrene, 28.8 g butadiene and 0.2 g azobisisobutyronitrile were mixed and heated at 40° C. for 6 hours, then cooled to room temperature, washed with acetone, and dried at 50° C. for 4 hours to obtain a polymer.

[0119] Step 2: 35 g of the polymer obtained in step 1, 50 g of flaky zinc powder, 3 g of YCK-2410 dispersant, 2 g of hydrogenated castor oil, 2 g of BYK-307 leveling agent, 2 g of BYK-141 defoamer, 2 g of antioxidant 168, 2 g of Y200 fumed silica coupling agent, and 2 g of DMP-30 curing accelerator are mixed to obtain component A.

[0120] Step 3: Mix 70 g of hexahydrophthalic anhydride curing agent and 30 g of ammonium chloride to obtain component B.

[0121] Step 4: Mix 100 g of component A with 30 g of component B to obtain a coating for offshore wind power.

[0122] Comparative Example 3

[0123] An anti-corrosion coating for offshore wind power generation was prepared according to the method of Example 1, except that the monovinyl aromatic structural unit was not used and was replaced by acrylamide shown in Formula III, that is:

[0124] Step 1: Under nitrogen protection, 70 g of acrylamide, 1 g of monomer (Formula IV, wherein p=2), 28.8 g of butadiene and 0.2 g of azobisisobutyronitrile were mixed and heated at 40° C. for 6 hours. The mixture was then cooled to room temperature, washed with acetone, and dried at 50° C. for 4 hours to obtain a polymer.

[0125] Step 2: 35 g of the polymer obtained in step 1, 50 g of flaky zinc powder, 3 g of YCK-2410 dispersant, 2 g of hydrogenated castor oil, 2 g of BYK-307 leveling agent, 2 g of BYK-141 defoamer, 2 g of antioxidant 168, 2 g of Y200 fumed silica coupling agent, and 2 g of DMP-30 curing accelerator are mixed to obtain component A.

[0126] Step 3: Mix 70 g of hexahydrophthalic anhydride curing agent and 30 g of ammonium chloride to obtain component B.

[0127] Step 4: Mix 100 g of component A with 30 g of component B to obtain a coating for offshore wind power.

[0128] Comparative Example 4

[0129] An anti-corrosion coating for offshore wind power was prepared according to the method of Example 1, except that the diene structural unit was not used and was replaced by acrylamide of formula III, that is:

[0130] Step 1: Under nitrogen protection, 58.8 g of acrylamide, 1 g of monomer (Formula IV, wherein p=2), 40 g of styrene and 0.2 g of azobisisobutyronitrile were mixed and heated at 40° C. for 6 hours. The mixture was then cooled to room temperature, washed with acetone, and dried at 50° C. for 4 hours to obtain a polymer.

[0131] Step 2: 35 g of the polymer obtained in step 1, 50 g of flaky zinc powder, 3 g of YCK-2410 dispersant, 2 g of hydrogenated castor oil, 2 g of BYK-307 leveling agent, 2 g of BYK-141 defoamer, 2 g of antioxidant 168, 2 g of Y200 fumed silica coupling agent, and 2 g of DMP-30 curing accelerator are mixed to obtain component A.

[0132] Step 3: Mix 70 g of hexahydrophthalic anhydride curing agent and 30 g of ammonium chloride to obtain component B.

[0133] Step 4: Mix 100 g of component A with 30 g of component B to obtain a coating for offshore wind power.

[0134] Comparative Example 5

[0135] An anti-corrosion coating for offshore wind power was prepared according to the method of Example 1, except that an anhydride curing agent was not used and was replaced by a cationic curing agent, namely:

[0136] Step 1: Under nitrogen protection, 30 g acrylamide, 1 g monomer (Formula IV, wherein p=2), 40 g styrene, 28.8 g butadiene and 0.2 g azobisisobutyronitrile were mixed and heated at 40° C. for 6 hours. The mixture was then cooled to room temperature, washed with acetone, and dried at 50° C. for 4 hours to obtain a polymer.

[0137] Step 2: 35 g of the polymer obtained in step 1, 50 g of flaky zinc powder, 3 g of YCK-2410 dispersant, 2 g of hydrogenated castor oil, 2 g of BYK-307 leveling agent, 2 g of BYK-141 defoamer, 2 g of antioxidant 168, 2 g of Y200 fumed silica coupling agent, and 2 g of DMP-30 curing accelerator are mixed to obtain component A.

[0138] Step 3: Take 100 g of ammonium chloride as component B.

[0139] Step 4: Mix 100 g of component A with 30 g of component B to obtain a coating for offshore wind power.

[0140] Comparative Example 6

[0141] An anti-corrosion coating for offshore wind power was prepared according to the method of Example 1, except that the cationic curing agent was not used and was replaced by an anhydride curing agent, namely:

[0142] Step 1: Under nitrogen protection, 30 g acrylamide, 1 g monomer (Formula IV, wherein p=2), 40 g styrene, 28.8 g butadiene and 0.2 g azobisisobutyronitrile were mixed and heated at 40° C. for 6 hours. The mixture was then cooled to room temperature, washed with acetone, and dried at 50° C. for 4 hours to obtain a polymer.

[0143] Step 2: 35 g of the polymer obtained in step 1, 50 g of flaky zinc powder, 3 g of YCK-2410 dispersant, 2 g of hydrogenated castor oil, 2 g of BYK-307 leveling agent, 2 g of BYK-141 defoamer, 2 g of antioxidant 168, 2 g of Y200 fumed silica coupling agent, and 2 g of DMP-30 curing accelerator are mixed to obtain component A.

[0144] Step 3: Take 100 g of hexahydrophthalic anhydride curing agent as component B.

[0145] Step 4: Mix 100 g of component A with 30 g of component B to obtain a coating for offshore wind power.

[0146] Comparative Example 7

[0147] Fluorinated coatings were purchased commercially.

[0148] Test Case

[0149] The coatings of Examples 1-9 and Comparative Examples 1-7 were tested for performance, respectively, and the drying time, adhesion, impact resistance, salt spray resistance, corrosion current density and corrosion potential were tested. The results are shown in Table 1.

[0150] (1) Drying time is tested according to GB / T 1728-2020 at a test temperature of 23±2℃.

[0151] (2) Adhesion was tested according to GB / T 5210-2006.

[0152] (3) Impact resistance is tested according to GB / T 1732-2020.

[0153] (4) Salt spray resistance is tested according to GB / T 1771-2007.

[0154] (5) Test method for corrosion current density and corrosion potential: The electrochemical properties of the coating were analyzed using an RST-3000 electrochemical workstation, with the coating obtained in the example or comparative example as the working electrode, a saturated calomel electrode as the reference electrode, Pt as the counter electrode, and a 3.5% NaCl solution as the medium.

[0155] Table 1

[0156]

[0157] It can be seen from the above table that the coating prepared by the formula of the present invention has the advantages of short drying time, strong adhesion, strong impact resistance, strong salt spray resistance, low corrosion current density and high corrosion potential. Compared with the commercially available fluorine-containing coating of Comparative Example 7, the corrosion resistance of the coating of the present invention is greatly improved, and the drying time, adhesion, impact resistance and salt spray resistance are not reduced, indicating that the coating for offshore wind power of the present invention has excellent performance.

[0158] The present application is not limited to the embodiments described above, and various modifications and changes may be made without departing from the scope thereof. The scope of the present application is limited only by the appended claims.

[0159] In the present application, each embodiment may focus on the differences from other embodiments, and the same or similar parts between the embodiments may refer to each other.

Claims

1. A coating for offshore wind power, comprising component A and component B, wherein: The component A comprises a polymer, flaky zinc powder and an additive, wherein the polymer contains a structural unit A represented by formula (I), a structural unit B represented by formula (II), a monovinyl aromatic structural unit and a diene structural unit; based on the weight of the polymer, the content of the structural unit A represented by formula (I) is 10-50% by weight, the content of the structural unit B represented by formula (II) is 0.1-2% by weight, the content of the monovinyl aromatic structural unit is 30-60% by weight, and the content of the diene structural unit is 18-40% by weight; wherein the component B is a curing agent; Here, p is an integer from 1 to 6.

2. The coating for offshore wind power according to claim 1, characterized in that: Based on the total weight of component A, the content of the polymer is 20-50 weight %, the content of the flaky zinc powder is 30-60 weight %, and the content of the auxiliary agent is 10-30 weight %.

3. The coating for offshore wind power according to claim 1 or 2, characterized in that: The auxiliary agent is selected from one or more of a dispersant, a thixotropic agent, a leveling agent, a defoaming agent, a coupling agent, an antioxidant and a curing accelerator.

4. The coating for offshore wind power according to claim 3 is characterized in that: The dispersant is selected from one or more of carboxylates, sulfates, sulfonates, quaternary ammonium salts and pyridinium salts; and / or, The thixotropic agent is selected from organic bentonite and / or hydrogenated castor oil; and / or, The leveling agent is selected from one or more of BYK-307, BYK-310, BYK-320 and BYK-333; and / or, The defoamer is selected from BYK-072 and / or BYK-141; and / or, The antioxidant is selected from antioxidant 168 and / or antioxidant 1010; and / or, The coupling agent is selected from silane coupling agents; and / or, The curing accelerator is selected from one or more of amines, phenols, substituted ureas, imidazoles and their salts, metal organic salts and phosphine compounds.

5. The coating for offshore wind power according to any one of claims 1 to 4, characterized in that: The curing agent is selected from an anhydride curing agent and / or a cationic curing agent; more preferably, the curing agent is selected from an anhydride curing agent and a cationic curing agent, and the weight ratio of the anhydride curing agent to the cationic curing agent is 1:0.2-0.6; More preferably, the anhydride curing agent is selected from one or more of phthalic anhydride, hexahydrophthalic anhydride, glutaric anhydride and dodecyl succinic anhydride; More preferably, the cationic curing agent is selected from one or more of aromatic sulfonium salts, aromatic iodonium salts, aromatic phosphonium salts, aluminum complex curing agents, aromatic diazonium salts and pyridinium curing agents.

6. The coating for offshore wind power according to any one of claims 1 to 5, characterized in that: The weight ratio of component A to component B is 1:0.1-0.

4.

7. The method for preparing the coating for offshore wind power according to any one of claims 1 to 6, comprising: Step 1, in the presence of an initiator, mixing a monomer having a structure represented by formula (III), a monomer having a structure represented by formula (IV), a monovinyl aromatic hydrocarbon structural unit and a diene structural unit to carry out a polymerization reaction to obtain a polymer, wherein the amount of the structural unit A represented by formula (III) is 10-50% by weight, the amount of the structural unit B represented by formula (IV) is 0.1-2% by weight, the amount of the monovinyl aromatic hydrocarbon structural unit is 30-60% by weight, and the amount of the diene structural unit is 18-40% by weight based on the weight of the polymer; Wherein, p is an integer from 1 to 6; Step 2, mixing the polymer, flaky zinc powder and an additive to obtain component A; Step 3: Mix component B with component A, wherein component B is a curing agent.

8. The preparation method according to claim 7, characterized in that: The initiator is selected from one or more of azobisisobutyronitrile, azobisisoheptanenitrile and dibenzoyl peroxide; Preferably, the amount of the initiator used is 0.1-0.3 wt % based on the total weight of the polymer.

9. The preparation method according to claim 6 or 7, characterized in that: The polymerization reaction conditions include: temperature of 10-40° C. and time of 6-10 hours.

10. Use of the coating for offshore wind power according to any one of claims 1 to 6 in the field of offshore wind power.

Citation Information

Patent Citations

  • Antiseptic wear-resisting freezing adhesion-resisting one coat paint and preparation method thereof

    CN102093812B

Cited By

  • Insulating, anti-corrosion and anti-condensation coating and preparation method thereof

    CN121343449A